2013
DOI: 10.5424/sjar/2013113-3842
|View full text |Cite
|
Sign up to set email alerts
|

Short communication. Impact of the amino acid proline on the cold hardiness of honey bee, Apis mellifera L.

Abstract: Like many insects, honey bee can increase its cold tolerance through freeze avoidance, using antifreeze proteins (AFPs) to lower its supercooling point (SCP). Proline is the most dominant amino acid in honey bee hemolymph, which can be obtained by the insect through feeding. In the current study the antifreeze activity of this amino acid was evaluated on worker honey bees, immediately before the start of cold season. The experiment was established on four treatments including three different concentrations of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…121 Forager preferences for AAs may come with benefits. Proline for 122 example, has been described as a flight muscle stimulant (Barker 123 and Lehner, 1972;Carter et al, 2006;Micheu et al, 2000; 124 Mollaei et al, 2013 material (Supplement 1: S1-a, S1-b and S1-c foragers in an artificial meadow (Fig. 2), they showed preferences 382 for higher sucrose concentrations (F 1,140 = 8.05, P = 0.005), and 383 simultaneously phenylalanine was a significant phagostimulant, 384 and glycine a phago-deterrent (F 2,140 = 30.9, P < 0.001; with post 385 hoc significances for both glycine < control and phenylala-386 nine > control).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…121 Forager preferences for AAs may come with benefits. Proline for 122 example, has been described as a flight muscle stimulant (Barker 123 and Lehner, 1972;Carter et al, 2006;Micheu et al, 2000; 124 Mollaei et al, 2013 material (Supplement 1: S1-a, S1-b and S1-c foragers in an artificial meadow (Fig. 2), they showed preferences 382 for higher sucrose concentrations (F 1,140 = 8.05, P = 0.005), and 383 simultaneously phenylalanine was a significant phagostimulant, 384 and glycine a phago-deterrent (F 2,140 = 30.9, P < 0.001; with post 385 hoc significances for both glycine < control and phenylala-386 nine > control).…”
mentioning
confidence: 99%
“…576 As mentioned, proline may be directly used as a minor source of 577 flight fuel (Barker and Lehner, 1972;Carter et al, 2006;Micheu 578 et al, 2000;Mollaei et al, 2013). However, the study by Mollaei Forager task specialization affects various physiological and 596 behavioral traits (Nelson et al, 2007;Page, 2013;Robinson and 597 Vargo, 1997).…”
mentioning
confidence: 99%
“…A substantial question within the current study addressed if AAs in nectar may affect the physiology and performance of bees. As mentioned, proline may be directly used as a minor source of flight fuel (Barker and Lehner, 1972; Carter et al, 2006; Micheu et al, 2000; Mollaei et al, 2013). However, the study by Mollaei et al (2013) showed no notable honey bee flight muscle stimulation at 0.1% proline treatment.…”
Section: Discussionmentioning
confidence: 99%
“…As mentioned, proline may be directly used as a minor source of flight fuel (Barker and Lehner, 1972; Carter et al, 2006; Micheu et al, 2000; Mollaei et al, 2013). However, the study by Mollaei et al (2013) showed no notable honey bee flight muscle stimulation at 0.1% proline treatment. In our homing studies proline at 0.1% did also not evoke an effect, neither on the return rate, nor the median flight time of bees (Table 1 and 3).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation